In their own voices : conversations with African emerging leaders - Bekenova, Kristina (Ibidem Press, 2019)
Kristina Bekenova presents a collection of interviews with fifteen African emerging leaders, young scholars and researchers, musicians, poets, artists, doctors, philanthropists, environmentalists, defenders of animal rights, tour operators, and treasurers of traditional culture, from the Democratic Republic of Congo, Ethiopia, the Gambia, Nigeria, Malawi, Rwanda, Somaliland, South Africa, South Sudan, and Zimbabwe. These interviews are an important, effective, and efficient way to make Africa's authentic voices heard. The interviewees explain what Africa needs most, what they are doing about it, what vision for Africa they have, and how they think their ideas can be implemented. They share genuine African bottom-up perspectives, voice their understanding of African natural and cultural issues, identify Africa's true needs, and formulate recommendations from an original African perspective. This book presents a unique opportunity to hear their message and to think more carefully about how we can help Africa along its developmental path.